Evaluation of temporal pattern properties of road accident based on fatality, road width and length / Nur Asmida Mohd Apandi - Mohd Apandi, Nur Asmida (2018)
This paper introduces about the study of temporal pattern properties of road accident that occur at Kedah state. Data sources of the road accident was obtaining from police department who consists of a data that describing a few factor such as types of accident, time and date of accident and address where it happened. Next, data visualization and analysis of the properties of temporal pattern road accident can be done using Geographical Information System (GIS) technology. Using this technology, it allows spatial analysis and spatial statistic that rely on geographically referenced data to be done so that better interpretation about the temporal pattern road accident can be achieved. The use of Geographical Information System (GIS) technology can provides the capability for capturing, storing, querying, analyzing and displaying geospatial data. Besides that, GIS also stand out for their ability of managing the geospatial data. Generally, geospatial data was function as to locate spatial features on the Earth’s surface and it can be done either by using a geographic or a projected coordinate system. In this paper, several GIS analysis methods had been used as to get a clear view about the properties of spatial temporal pattern of road accident at Kedah state. Hotspot analysis of Getis-Ord Gi* had been used as to determine the hotspot area of road accident cases occurrences. This may reflect with the result show the hot and cold area represent the frequency of it happened. Spatial analyst by using point density was performed in order to shows the relation between the effect of road accident on types of fatality based on types of road. Many previous study introduce GIS only for determination of the hotspot area but on this study it tells more about an analysis of road accident based on its temporal pattern properties.